Chito-oligosaccharide composites enhanced the adaptability of cotton seedlings to salinized soil by modulating photosynthetic efficiency and metabolite - Mengjie An; Linlin Zhang; Qianqian Wang; Kaidi Ren; Qinjuan Wang; Dongmei Lin; Yongqi Zhu; Yonghong Fan (Frontiers in Plant Science, 2025)
Agricultural production on salinized lands is an important direction of current agricultural research. Chito-oligosaccharide has been used as an excellent soil amendment in recent years. However, the mechanism of chito-oligosaccharide composites (COS-PA) impacting cotton seedlings on salinized lands is still unclear. In this study, the metabolic mechanism of COS-PA regulating cotton salt stress resistance was investigated by measuring seedling growth, leaf ion content, photosynthetic characteristics, and widely-targeted metabolic profiles. The results showed that salt stress reduced the contents of K+ and Ca2+ and enhanced the content of Na+ in cotton leaves compared to the control, which inhibited leaf photosynthesis and seedling growth. COS-PA application decreased leaf Na+ content significantly in salt-stressed cotton seedlings by 69.70%, and increased the leaf Ca2+ content, fresh weight of each plant part, transpiration rate, leaf chlorophyll concentration (Chl a), actual quantum yield, as well as stomatal conductance by 7.22%, 46.33%-96.36%, 96.65%, 44.53%, 27.15%, and 168.24%, respectively, compared with the no COS-PA application treatment. COS-PA application regulated the abundances of key leaf metabolites (L-lactic acid, Succinic acid, Methylmalonic acid, Aconitic acid, Citraconic acid), alleviating the salt stress. Therefore, COS-PA application could improve cotton seedling’s salt stress resistance by adjusting the growth characteristics, photosynthetic characteristics, and carbohydrate metabolism of cotton seedlings. The research will advance understanding of mechanisms by which COS-PA regulates the salt stress resistance of cotton seedlings and offer a scientific basis for salinized soil remediation and cotton yield improvement in arid areas.